The time traveler's wife : the complete series [videorecording (DVD)] - Moffat, Steven, 1961-; Leslie, Rose, 1987-; James, Theo, 1984-; Borges, Desmin; Lopez, Natasha; Niffenegger, Audrey (Warner Bros. Entertainment, 2022)
The out-of-order love story between Clare and Henry is as complicated as his attempts to explain his "condition" -- a tendency to get displaced in time when he becomes too emotional. Despite the odds, the woman who has known her husband since she was 6 and he was 40, and the 20 year old man who meets a beautiful redhead for the first time at his library job, manage to make a life and love worth having.